2018
DOI: 10.1111/cup.13265
|View full text |Cite
|
Sign up to set email alerts
|

Influence of variability in assessment of Breslow thickness, mitotic rate and ulceration among US pathologists interpreting invasive melanoma, for the purpose of AJCC staging

Abstract: Variability in the staging of T1 melanoma among pathologists when using the AJCC seventh edition criteria is closely related to the detection of mitotic figures, with BT playing a less prominent role. Decreased variability is expected after implementation of the eighth edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Standardized BT is achieved through the use of an ocular micrometer measuring from the top of the granular cell layer of the epidermis to the deepest point of the invasion of the tumor (Breslow, 1975;Scolyer et al, 2013). The correct evaluation of BT is of critical importance because it can influence patient clinical assessment, prognostication, and management (Elmore et al, 2017;Lo et al, 2018;Niebling et al, 2013;Taylor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized BT is achieved through the use of an ocular micrometer measuring from the top of the granular cell layer of the epidermis to the deepest point of the invasion of the tumor (Breslow, 1975;Scolyer et al, 2013). The correct evaluation of BT is of critical importance because it can influence patient clinical assessment, prognostication, and management (Elmore et al, 2017;Lo et al, 2018;Niebling et al, 2013;Taylor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interobserver variability of BT may arise from differing levels of expertise among pathologists, though latest studies demonstrated an improvement in reproducibility (Bhoyrul et al, 2019;Elmore et al, 2018Elmore et al, , 2017Niebling et al, 2013;Taylor et al, 2018). Whether other specific pathologic features associated with BT, such as the presence of regression, periadnexal extensions of malignant melanocytes, and lymphocyte infiltrate, may influence melanoma prognosis is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, treatment lasts one year and costs run over $20,000 per patient per month (2). Given that death rates from melanoma at 10 years range from 2% to 8% for stage I disease, 12%-25% for stage II disease, and 12%-40% for stage III disease, treating all patients with early-stage melanoma would result in significant overtreatment and resource expenditure (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The current clinical criterion for evaluating risk of recurrence is the American Joint Committee on Cancer (AJCC) staging system (3,4). The AJCC staging system includes multiple parameters including depth of the primary tumor, ulceration, mitotic rate, and local or nodal metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation